2011
DOI: 10.1093/eurheartj/ehr433
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist intervention in primary care to improve outcomes in patients with left ventricular systolic dysfunction

Abstract: A low-intensity, pharmacist-led collaborative intervention in primary care resulted in modest improvements in prescribing of disease-modifying medications but did not improve clinical outcomes in a population that was relatively well treated at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 32 publications
2
80
0
Order By: Relevance
“…47 Studies have also evaluated pharmacist-managed medication titration in HF. 37,38 Recognising the key role that general practitioners (GPs) play in HF management, Lowrie et al undertook a cluster-RCT of nonspecialist, pharmacist-managed medication titration in 1,090 HFrEF patients attending 87 practices in United Kingdom. While this study did not achieve its primary clinical endpoint, a higher proportion of patients who enrolled in practices with pharmacist-assisted titration achieved target doses of ACEI therapy.…”
Section: Medication Titration Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Studies have also evaluated pharmacist-managed medication titration in HF. 37,38 Recognising the key role that general practitioners (GPs) play in HF management, Lowrie et al undertook a cluster-RCT of nonspecialist, pharmacist-managed medication titration in 1,090 HFrEF patients attending 87 practices in United Kingdom. While this study did not achieve its primary clinical endpoint, a higher proportion of patients who enrolled in practices with pharmacist-assisted titration achieved target doses of ACEI therapy.…”
Section: Medication Titration Intervention Studiesmentioning
confidence: 99%
“…There were favourable trends for beta-blocker titration, however these did not achieve statistical significance. 38 In a before-after, retrospective design study targeting 51 higher-risk HFrEF patients conducted in the United States, Martinez et al demonstrated that a multifaceted intervention, which included pharmacist-managed titration guided by telephone monitoring, resulted in a higher proportion of patients achieving target doses of ACEI/ARB and beta-blockers. 37 We recently undertook a quality improvement study that aimed to embed a pre-designed medication titration plan into standard clinical practice for patients newly referred to the HF services in three hospitals.…”
Section: Medication Titration Intervention Studiesmentioning
confidence: 99%
“…However, no difference in composite endpoint comprising death or hospitalisation due to worsening of HF symptoms was observed between the study and control groups despite covering large groups of patients, i.e. more than 1000 per group, and long follow-up of 4.7 years [23]. It is worth asking the question about the cost-effectiveness of pharmaceutical care.…”
Section: The Role Of the Pharmacist In The Treatment Of Cvdmentioning
confidence: 99%
“…Eventually, pharmaceutical intervention can effectively increase the level of compliance of pharmacotherapy with current guidelines -which by definition means optimising pharmacotherapy in accordance with the principles of evidence-based medicine [22]. Interesting in this context is the study conducted by Lowrie et al [23] in the setting of patients using drugs recommended by current guidelines. Despite this, the intervention of a pharmacist has brought improvement in compliance of pharmacotherapy.…”
Section: The Role Of the Pharmacist In The Treatment Of Cvdmentioning
confidence: 99%
“…1 There are also plans to address important safety issues in India through prospective monitoring programs.…”
mentioning
confidence: 99%